2021
DOI: 10.1002/pip.3396
|View full text |Cite
|
Sign up to set email alerts
|

Temperature coefficients of degraded crystalline silicon photovoltaic modules at outdoor conditions

Abstract: The temperature effect on photovoltaic modules is usually quantified by means of some coefficients relating the variations of the open‐circuit voltage, of the short‐circuit current, and of the maximum power to temperature changes. In this paper, comprehensive experimental guidelines to estimate the temperature coefficients when measurements are performed outdoors are given. In addition, a correction procedure is applied to the short‐circuit current to cancel out the influence of the fluctuations in the irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…From the results of this comparative, we must conclude, as other authors have stated in the literature, 53 that there is a dependence of the estimated degradation rate on the method of correction used, and this fact requires further study. One possible reason are the high uncertainty associated to the determination of the required parameters to apply some of these methods, 54 In any case, in order to identify the most suitable correction procedure to be used when estimating degradation rates, it is necessary to perform a detailed comparative study among all the several approaches published in the literature, even testing them with modules of different technologies. This can be done using each correcting method to translate an initial measured curve to the conditions of another target curve, also measured, and comparing the corrected curve to the measured target one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the results of this comparative, we must conclude, as other authors have stated in the literature, 53 that there is a dependence of the estimated degradation rate on the method of correction used, and this fact requires further study. One possible reason are the high uncertainty associated to the determination of the required parameters to apply some of these methods, 54 In any case, in order to identify the most suitable correction procedure to be used when estimating degradation rates, it is necessary to perform a detailed comparative study among all the several approaches published in the literature, even testing them with modules of different technologies. This can be done using each correcting method to translate an initial measured curve to the conditions of another target curve, also measured, and comparing the corrected curve to the measured target one.…”
Section: Discussionmentioning
confidence: 99%
“…From the results of this comparative, we must conclude, as other authors have stated in the literature, 53 that there is a dependence of the estimated degradation rate on the method of correction used, and this fact requires further study. One possible reason are the high uncertainty associated to the determination of the required parameters to apply some of these methods, 54 specially if their determination is performed based on outdoor measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the TC of solar cell modules, the characteristics of solar cell modules are recorded in the range of 25 • C-65 • C, with an interval of 1 K and irradiance of 1000 W cm 2 , according to the IEC60891 [22]. In this paper, the experimental data for TCs of various solar cell modules [16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] are compared with the calculated results. According to Piliougine et al [23], TCs of Si solar cell modules are shown to be constant in the temperature range between 28 • C and 48 • C. However, the poorer performance Si and Ge solar cells have shown further poorer TCs for open-circuit voltage and fill factor in the higher temperature range above 360 K according to Singh and Ravindra [24].…”
Section: Analysis Of Tcs Of Solar Cell Modules Towards Development Of...mentioning
confidence: 99%
“…In this paper, the experimental data for TCs of various solar cell modules [16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] are compared with the calculated results. According to Piliougine et al [23], TCs of Si solar cell modules are shown to be constant in the temperature range between 28 • C and 48 • C. However, the poorer performance Si and Ge solar cells have shown further poorer TCs for open-circuit voltage and fill factor in the higher temperature range above 360 K according to Singh and Ravindra [24]. Therefore, vehicles need better performance and better TC solar cell modules on hot days.…”
Section: Analysis Of Tcs Of Solar Cell Modules Towards Development Of...mentioning
confidence: 99%
“…However, these techniques lack flexibility and generally have high costs associated 6,7 . From a thermal perspective, thermocouples, resistive‐based temperature detectors (RTDs) or infrared thermography can be used to monitor temperature variations during processing and in the field 8–10 . Incorporating large quantities of these sensors on to or into the laminate can be quite invasive while (dis)continuous outdoor monitoring using thermography can be costly and impractical.…”
Section: Introductionmentioning
confidence: 99%